Social networks on trial. Addictive patterns, data and responsibility in the attention economy - Herrero Suárez, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The emergence of the large social networking technology platforms has had a profound impact on communication and social interaction. Alongside their undeniable benefits, a series of risks or possible negative effects associated with them have also been identified. Although initially the negative side of social networks focused on the misuse of personal data and the violation of their users’ right to privacy, in recent years other issues, especially the risks of addiction and damage to mental health, are entering the debate on their dangers. The aim of this work is to critically analyse this risk and the possibilities for action from the legal system to solve or mitigate it. To this end, it starts from the examination and assessment of the various legal actions taken against the main social networks, especially in the USA, known as the social media addiction lawsuits, examining their viability and the possibility of transferring them to our legal system.
Keywords: social networks; adicition; damages; attention economy; algorithm